Non-chemical insect pest management - Ignacimuthu, S.; David, B. Vasantharaj (New Delhi : Elite Publishing House, 2010)
Papers presented at the National Symposium on'Non-Chemical Insect Pest Management' held at Chennai.
Plant based pesticides -- Microbial pesticides -- Biological control -- Cultural control and transgenics -- Pheromones, attractants and repellents.
Includes bibliographical references and index.
Keywords: Insect pests -- Biological control -- India -- Congresses; Insect pests -- Cultural control -- India -- Congresses